"It's the Lack of Structure that's Causing the Problem": Managerial Competence, the Treatment of Workers, and Job Stress in Precarious Firms. (June 2018) - Shuey, Kim M.; Gordon, Catherine; McMullin, Julie A.
In this study, we use Hodson's concept of Management Citizenship Behavior (MCB) and a case study research design of 16 small Canadian information technology (IT) firms to examine the interrelationship between insecure work environments, management behavior, and job stress within the context of the organizations. Within the study firms, the presence of MCB in the form of competent and respectful management was associated with a positive work environment and less job stress. The relationship between insecurity and stressful work environments was less straightforward and could only be understood in combination with MCB. Findings suggest that management behavior may moderate the relationship between precarious employment and stress, particularly within the context of small firms in a sector that is an important exemplar of work in the new economy. Competent and respectful management practices may alleviate the stress associated with job insecurity within precarious firms, and in contrast, their absence may create a pervasive culture of stress even within stable firms. Results indicate the importance of studying the organizational context established by the actions of owners and managers and suggest that good management can create healthier work environments even within the context of otherwise harmful job conditions.